Silent myocardial ischemia in patients with diabetes mellitus type 2 - Koshlia, V. I.; Martynenko, A. V. (Zaporozhye Medical Journal, 2015)
Increased interest to the high prevalence of the phenomenon of silent myocardial ischemia was detected nowadays in the literature. Aim. To study role of the diabetes mellitus in the development of the silent myocardial ischemia. To underline main patophysiological features, diagnostic approaches and main streams in the treatment. Methods and results. Literature review of the Ukrainian and foreign issues. Results. Special place among the risk factors for CHD is type 2 diabetes takes silent myocardial ischemia. The prevalence of silent myocardial ischemia in patients with diabetes is significantly higher (2-7 times) than in those without diabetes. Many attribute this to the higher incidence of atherosclerosis and coronary heart disease in the general population in diabetic patients, but attention is drawn to a complication of diabetes - diabetic autonomic neuropathy, particularly cardiovascular its shape. Analysis of the literature showed that, despite the obvious successes in the study of SMI, still remain differences in views on the possible causes and mechanisms of this phenomenon CHD. Conclusion. The literature review provides information about the pathophysiological features of SMI in diabetes mellitus type 2, presented data on its prevalence, methods of diagnosis and treatment of the main directions reflected the prognostic significance of silent myocardial ischemia in patients with type 2 diabetes.